IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM RANGKA PENATAAN PASAR TRADISIONAL DAN PASAR MODERN DI KABUPATEN JEPARA - Turnip, Devi Evifani; Adhi, Suwanto; Harsasto, Priyatno (Journal of Politic and Government Studies, 2016)
ABSTRACT Implementation of Local Government in the framework of the arrangement of traditional markets and modern markets in Jepara regency has the aim to determine the policy implementation process in protecting traditional markets dam arrangement of the modern market, to know, to know the effort to empower traditional traders and knowing implementing policies in protecting against traditional markets and modern markets structuring. Methods of execution in this study using a qualitative descriptive study with primary data types are the words and actions. Sources of data obtained derived from primary and secondary data. To search for informants in this study is conducted with a purposive sample (making intentional) and accidental sampling (sampling by accident when he met at the study site). Techniques for collecting data later using interviews, observation and documents. Structuring traditional market and modern market in Jepara district is one of the government's policy which aims to make the arrangement of traditional markets and modern markets, but in fact in the process of implementing its policies are not appropriate where there is still a traditional market that is not well ordered and market presence more modern and within walking distance of traditional markets made some traders complained because their incomes to decrease. Structuring the market Traditional has not done well because the budget is not adequate and human resources that traditional traders still difficult to style, it is because the absence of development programs for merchants Traditional to improve the quality of the arrangement of the market Traditional hence the existence of traditional markets unbeaten with presence modern market in the district of Jepara Keywords: Government Policies, Markets Structuring Traditional and Modern Markets